The Role of Virtual Accounts for Policyholders in Islamic and Conventional Insurance - Muhamad Susandra Rohmandika; Teuku Ghufran TS; Yusuf Falaqi Ahmad (Maliki Islamic Economics Journal, 2021)
Virtual Account is one of the payment tools that is currently trending. The use of a Virtual Account brings many benefits, including for insurance institutions and policyholders. However, several insurance institutions have not implemented or have not maximized the use of Virtual Accounts in their operational activities. This research aims to find out how important Virtual Account is for policyholders. This research is quantitative research using a descriptive analysis approach through Google Form media to 108 policyholders at an insurance institution. This study proves that insurance institutions need to implement and maximize the use of Virtual Accounts in each of their activities.